2017
DOI: 10.1051/matecconf/201712502022
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate study of spectral data of oils

Abstract: Abstract. In this paper the study of structural differences and thermal degradation of edible oils during heating is presented. The study is performed on five types of vegetable oil: extra virgin olive oil, pomace olive oil, sunflower, canola and palm oil. The oils were measured by Raman spectroscopy. This method brings advantages as rapidity, independence on chemicals, provides specific information on chemical composition and structure of material and is able to detect structural changes. For the processing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This shows that the resulted peaks of palm frying oil in this study might indicate the significant Raman spectra characteristics of vegetable oils. Similar pattern of Raman spectrum of palm oil which exhibited the similar significant peaks were also reported in other studies [17,[19][20]. There were also studies which reported some similar patterns of the Raman spectra of animal fats or oils such as desi ghee, pork lard, beef tallow, duck oil and chicken fat [21][22].…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This shows that the resulted peaks of palm frying oil in this study might indicate the significant Raman spectra characteristics of vegetable oils. Similar pattern of Raman spectrum of palm oil which exhibited the similar significant peaks were also reported in other studies [17,[19][20]. There were also studies which reported some similar patterns of the Raman spectra of animal fats or oils such as desi ghee, pork lard, beef tallow, duck oil and chicken fat [21][22].…”
Section: Resultssupporting
confidence: 81%
“…At Raman peak of 1303 cm -1 , it was reported that the peak is assigned for the vibration of saturated CH2 in-plane twist [17]. The region from 1640 cm -1 to 1680 cm -1 reported to be the C=C stretching region to detect cis or trans isomers [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectroscopy has a great potential in nondestructive material analysis. This experience we already have with other type of surveyed materials [9,10]. Therefore its application on electronic components is being studied to extend the range of methods for deviation detection from original electronic components.…”
Section: Raman Spectroscopymentioning
confidence: 99%